The impact of media representations of the EU and its policies on European identity - Triga, Vasiliki; Vadratsikas, Konstantinos (My University, 2016)
The primary goal of this paper is to review the literature on the impact of media representations of the EU and its policies on processes of European identity building. More specifically, the central scope of the review is to discuss previous studies using methodological frameworks similar to the COHESIFY project with the aim to examine their usefulness as well as their weaknesses in order to assess how media representations of the EU policies impact on citizens’ identification with the EU. Based on the existing typologies for the analysis of media effects, the last section proposes an analytical framework for a more systematic study of media representations of the EU Cohesion policy and their effect on citizen’s identification with the EU.